Nephtyidae (Annelida: Polychaeta) from the Campos Basin, including two new species and a new record - Franco, Natália Bizzo; Rizzo, Alexandra E. (Zootaxa, 2016)
Members of the marine polychaete family Nephtyidae are commonly found in soft substrates. Their most distinctive characteristic is the presence of interramal branchiae located between the notopodia and neuropodia. In the present study, five species of Nephtyidae: Aglaophamus fabrun sp. nov., Aglaophamus juvenalis (Kinberg, 1866), Inermonephtys inermis (Ehlers, 1887), Inermonephtys soldius sp. nov. and Nephtys squamosa Ehlers, 1887 were found in the Campos Basin, state of Rio de Janeiro, including two new species and a new record for the Brazilian coast. Aglaophamus fabrun sp. nov. has a proboscis with 10 pairs of distal papillae and approximately 20 subdistal papillae in rows, with 3–5 papillae in each row; and lacks an unpaired median papilla; the prostomium has a pair of eyes and a characteristic pigmentation pattern. Inermonephtys soldius sp. nov. has interramal branchiae starting from parapodium 5, and basal papillae starting on chaetiger 6. Inermonephtys inermis is a new record for the Brazilian coast. Descriptions, comments and a key to species of Nephtyidae recorded from Brazil are provided.
World Polychaeta Database (WPolyDb)